EFEKTIFITAS PENGGUNAAN MEDIA PUZZEL ANGKA DIGITAL UNTUK MENINGKATKAN KEMAMPUAN MENGENAL BENTUK ANGKA BAGI ANAK TUNAGRAHITA RINGAN - Rizki -; Irdamurni -; Rahmahtrisilvia - (Jurnal Penelitian Pendidikan Khusus, 2013)
ABSTRACT This research background by the problems that researchers find in SLB mutiara Lubuk Alung Budi, a child's mild mental retardation in SLB class III semester who have problems in identifying the form numbers, it is first seen when researchers looked at the implementation of the ongoing learning of mathematics in the classroom III in SLB Pearl Budi Lubuk Alung, after apparently observed the child had difficulty in identifying the form numbers so when asked to show and write the child has difficulty. Under these conditions, the study aims to prove the effectiveness of the use of Digital Media Puzzle figure to improve the rate of child recognize shapes mild mental retardation SLB class III in mutiara Budi Lubuk Alung.This research Single Subject Research approach, the ABA design and data analysis techniques using visual analysis chart. Subjects were mild mental retardation children class III, where the child was told to show, and write the number corresponding shape, dictated many numbers are ten-digit numbers from 1 to 10 per meeting. Measurement of variables by using a percentage figure how many pieces can be known children according to their shape. The results of this study indicate that the Digital Media Puzzle Figures effective in improving the ability to know the form of the numbers in the teaching of mathematics to children third grade mild mental retardation SLB mutiara Budi Lubuk Alung. Observations made with the first three sessions, the session before being given intervention baseline (A1) conducted five times observation, the percentage of the ability to know the form number on this condition lies in the range of 5%, and 10%. Second, the intervention sessions (B) using the Digital Media Puzzle Figures observation carried seven times, ability to recognize shapes percentage points in this condition lies in the range of 30%, 30%, 40%, 60%, and 90%. Third session baseline (A2) is done five times of observation, the results obtained in the child's ability to recognize the form of increased numbers that lie in the range of 90% to 100%. Based on these results it can be concluded Puzzle Numbers Digital media is effective in improving the ability to know the form of mild mental retardation points for third grade children SLB mutiara Budi Alung depths. Suggested the teachers should be able to use the Digital Media Puzzle Figures in identifying the form numbers on the child's mild mental retardation. Kata Kunci : Tunagrahita Ringan ; kemampuan ; bentuk angka ; Puzzle Angka     Digital